2018
DOI: 10.1891/1052-3073.29.1.68
|View full text |Cite
|
Sign up to set email alerts
|

Two Year Sustainability of the Effect of a Financial Education Program on the Health and Wellbeing of Single, Low-Income Women

Abstract: Financial stress is implicated in poor health and decreased Quality of Life (QOL). The purpose of this project was to assess the 2-year effect of a financial education program on the health of single, low-income women. A total of 30 women were enrolled and 20 continued through follow-up. Two years following intervention, women demonstrated a $8,026 increase in mean annual income and significant improvements in health-related QOL and hopefulness. Half of the participants lost weight, and while not statistically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 8 publications
0
18
1
Order By: Relevance
“…Although the relationship is bidirectional, strategies which reduce financial stress are reported to result in physical and mental health gains. For example, according to White et al (2018) financial education programs in twenty single low income African American women improved their wellbeing and health. Collins & O'Rouke (2011) , in a review of US homeownership education and counselling programs reported that they are effective at improving timely payments and thereby housing security.…”
Section: Discussionmentioning
confidence: 99%
“…Although the relationship is bidirectional, strategies which reduce financial stress are reported to result in physical and mental health gains. For example, according to White et al (2018) financial education programs in twenty single low income African American women improved their wellbeing and health. Collins & O'Rouke (2011) , in a review of US homeownership education and counselling programs reported that they are effective at improving timely payments and thereby housing security.…”
Section: Discussionmentioning
confidence: 99%
“…26 Organizations embedding financial coaching services into existing job training and placement programs also increased individuals' financial security. 27 While the health effects of financial coaching are promising 28 and further studies are underway, 2324 proxy measures of mental health such as worry and stress have shown clear improvements in a randomized trial of financial coaching. 26 Credit counseling and programs building credit for communities historically marginalized by financial institutions can help achieve financial stability.…”
Section: Financial Services Improve Client Finances and Health Outcomesmentioning
confidence: 99%
“…Nonrandomized pilot data indicates that women who participate in the FSP are successful in making positive financial and health behavior changes. 7,8 While the Finances First study analysis is ongoing, both financial behaviors and healthy lifestyle behaviors are under investigation. A 20-year longitudinal study comparing the cardiovascular health outcomes of women who complete the FSP compared with matched controls is also underway.…”
Section: Implications and Future Researchmentioning
confidence: 99%